Efektivitas Projek Penguatan Profil Pelajar Pancasila dalam Menanamkan Nilai Karakter Peserta Didik di TK PKK Kota Batu - Asmah, Ayu; Supatmijati, Supatmijati (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2024)
This study aims to evaluate the effectiveness of the Projek Penguatan Profil Pelajar Pancasila (P5) in instilling character values at PKK Kindergarten Batu City, focusing on the theme “I Love Indonesia” and the corn sub-topic. The research method used was a qualitative approach with a case study design, involving 30 learners, two teachers, and the principal as research subjects. Data were collected through observation, interviews, and documentation, which were then analyzed using the Miles and Huberman interactive analysis model. The results showed that this project succeeded in creating an interactive, meaningful and fun learning atmosphere, where children were actively involved in corn food processing activities. P5 results showed an increase in the ability of students in terms of academics and the development of character values of cultural respect, mutual cooperation, critical reasoning. Interviews with teachers and principals revealed that this project serves as an effective means to instill character values in learners, with improved collaboration and communication skills among learners. In addition, documentation shows that children are able to process and produce work that reflects understanding in accordance with the project theme. This study concludes that the Pancasila Learner Profile Strengthening Project at PKK Kindergarten Batu City can be used as a good model for early childhood character development in the context of education in Indonesia.